2016
DOI: 10.1177/0148607116633823
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Bioelectrical Impedance Analysis in Patients Equipped With Implantable Cardioverter Defibrillators

Abstract: BIA can be safely performed in patients equipped with ICDs without cardiac monitoring. Current guidelines should be updated accordingly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 12 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…However, since these arrhythmias occurred more than 30 minutes after the BIA measurement in patients with a recent history of arrhythmias, they were likely coincidental and not induced by BIA. Consistently, Meyer et al reported no evidence of artefacts from BIA in the intracardiac electrograms of their stable outpatient cohort 28 …”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…However, since these arrhythmias occurred more than 30 minutes after the BIA measurement in patients with a recent history of arrhythmias, they were likely coincidental and not induced by BIA. Consistently, Meyer et al reported no evidence of artefacts from BIA in the intracardiac electrograms of their stable outpatient cohort 28 …”
Section: Discussionmentioning
confidence: 57%
“…Since the electrodes of the BIA device are placed on the hands and feet, this observation supports our findings. Moreover, BIA measurements have been rated as safe in small clinical study which found no evidence of interference with ICDs or CRT‐Ds and no change in ICD and CRT lead impedance during the measurement, even after setting the threshold to maximum sensitivity 28,33 …”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, 63 patients implanted with various single-chamber, dual-chamber and biventricular ICDs from different manufacturers underwent BIA measurements in concomitance with routine ICD controls [30]. The study revealed no electromagnetic interferences or artifacts during real-time electrocardiogram recordings using an electrical current of 0.8m Amp at frequencies from 5-100 kHz.…”
Section: Table 1: Patient Characteristicsmentioning
confidence: 91%
“…Bioimpedance spectroscopy is typically not performed on individuals with amputations and implanted metallic devices, although it can be safely performed for patients with ICDs. 23 Lung ultrasound is performed by the clinician using a linear or phased-array probe to detect the presence of B-lines. The presence of many B-lines increases the likelihood that a patient is above their dry weight.…”
Section: Returning To the Casementioning
confidence: 99%